Cryptococcosis: epidemiology, fungal resistance, and new alternatives for treatment - Gullo, F. P. [UNESP]; Rossi, S. A. [UNESP]; Sardi, J. de C. O. [UNESP]; Teodoro, V. L. I. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Fusco-Almeida, A. M. [UNESP] (Springer Nature, 2013)
Cryptococcosis is an important systemic mycosis and the third most prevalent disease in human immunodeficiency virus (HIV)-positive individuals. The incidence of cryptococcosis is high among the 25 million people with HIV/acquired immunodeficiency syndrome (AIDS), with recent estimates indicating that there are one million cases of cryptococcal meningitis globally per year in AIDS patients. In Cryptococcus neoformans, resistance to azoles may be associated with alterations in the target enzyme encoded by the gene ERG11, lanosterol 14α-demethylase. These alterations are obtained through mutations, or by overexpressing the gene encoding. In addition, C. gattii and C. neoformans present a heteroresistance phenotype, which may be related to increased virulence. Other species beyond C. neoformans and C. gattii, such as C. laurentii, have been diagnosed mainly in patients with immunosuppression. Infections of C. albidus have been isolated in cats and marine mammals. Recent evidence suggests that the majority of infections produced by this pathogen are associated with biofilm growth, which is also related with increased resistance to antifungal agents. Therefore, there is a great need to search for alternative antifungal agents for these fungi. The search for new molecules is currently occurring from nanoparticle drugs of plant peptide origin. This article presents a brief review of the literature regarding the epidemiology of cryptococcosis, as well as fungal resistance and new alternatives for treatment. © 2013 Springer-Verlag Berlin Heidelberg.